Application of Areca Peeler Skin Tools to Improve Community Productivity in Nagari Bukik Sikumpa Lima Puluh - Hendri Nurdin; Waskito Waskito; Hasanuddin Hasanuddin; Delima Yanti Sari (Universitas Negeri Padang, 2020)
Areca Catechu is a commodity of West Sumatra plantation in addition to other plantation crops. The process of stripping the areca nut is still conventional, requiring high labor and high costs. This has an impact on the income of the farming community in Nagari Bukik Sikumpa. Application of areca nut peeler technology in an effort to increase community productivity as a solution to overcome these problems. Efficient and constructive areca peeler with a gasoline motor drive of 6.5 PK and 3600 rpm rotation. The capacity of betel nut peelers is 5 kg with 5 minutes of continuous processing time. With the application of science and technology, it has an impact on people's welfare. It is expected that insights and mindsets in the community can be developed. With the existence of this skin stripper can help the community in processing the areca yield so that the work can be lighter and get maximum production